Sentimental Twain : Samuel Clemens in the Maze of Moral Philosophy - Camfield, Gregg (University of Pennsylvania Press, 2016)
In Sentimental Twain, Gregg Camfield examines the major and minor works of Mark Twain to redraw the boundaries between sentimentalism and realism in the second half of the nineteenth century.